DAMPAK POLA ASUH ORANG TUA PENGGANTI TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK DI SDN 1 KALIBEBER MOJOTENGAH - Dzawi Hizbatul Maola; Dyian Triyani; Hidayatu Munawaroh (INSTRUKTUR, 2023)
Parents, especially mothers, play an important role in shaping children's behavior. Physical, psychological and behavioral development must be properly considered for the survival of children. However, if the child's parents are not there, of course the child needs a substitute role figure who will educate and accompany him. The aim of the study was to analyze the adoption of parenting styles and the impact of surrogate parenting on the psychosocial development of children in an elementary school in the Mojotengah sub-district. This research uses a qualitative approach with a descriptive type. Data collection was done through semi-structured interviews with nine informants, namely fathers, grandmothers and aunts. Data analysis techniques using Miles Huberman's interactive model include data reduction, data display, and data verification. The research finding is that caregivers of children who are raised by biological parents have a tendency to use democratic rather than authoritarian and permissive parenting styles. Democratic parenting is characterized by giving encouragement and support for every positive activity carried out by children. Authoritarian parenting places more emphasis on children being obedient while permissive parenting by giving excessive affection without any guidance. The three parenting styles have positive and negative impacts on children. The positive impact that children receive such as enthusiasm in school, learning, worship, good social behavior, loving and caring for the surrounding environment. The negative impact on some children is spoiled behavior, lack of independence, and lack of courage. Thus, the application of democratic parenting as the right choice used by caregivers has a positive impact on the behavior of children who are not cared for by their own biological parents